Human rights and development in international law - Karimova, Tahmina (Abingdon, Oxon ; New York, NY : Routledge, 2016)
This book addresses the legal issues raised by the interaction between human rights and development in contemporary international law. In particular, it charts the parameters of international law that states have to take into account in order to protect human rights in the process of development. In doing so, it departs from traditional analyses, where human rights are mainly considered as a political dimension of development. Rather, the book suggests focusing on human rights as a system of international norms establishing minimum standards of protection of individuals and minimum standards applicable in all circumstances on what is essential for a dignified existence. The various dimensions covered in the book include: the discourse on human rights and development interrelationship, particularly opinio juris and the practice of states on the question; the notion of international assistance and cooperation in human rights law, under legal regimes such as international humanitarian law, and emerging rules in the area of protection of persons in the event of disasters; the extraterritorial scope of economic, social and cultural rights treaties; and legal principles on the respect for human rights in externally designed and planned development activities. Analysis of these topics sheds light on the question of whether international law as it stands today addresses most of the issues concerning the protection of human rights in the development process.--
Development from a human rights perspective -- The right to development -- The obligation of international assistance and cooperation -- $t New legal ideas : comment on the relationship of the international assistance and cooperation and extraterritorial scope of ESC rights -- Respect for human rights in external activities : overarching normative principles.
Includes bibliographical references and index.
Keywords: Human rights; Right to development; International law; International cooperation; Human rights; International cooperation; International law; Right to development